Automotive Industry in Istanbul and Eastern Marmara Region: An Innovative Cluster? - Ayse Nur Albayrak; Gulden Erkut (European Regional Science Association (ERSA), 2010)
Innovativeness being the main driver of the competitiveness of a region has been created by different actors such as firms, research centers, universities and other public or private institutions interacting on various levels. Spatial concentration accelerated these interactions and the potential of innovativeness increased in these clusters by sharing inputs, benefiting from labor pools and dispersing knowledge. Both government intervention and local characteristics determine success of the clusters. This study has focused on the automotive industry which is clustered in Istanbul and Eastern Marmara Region in Turkey. Not only automotive industry but also other related industries have been clustering in this region since an important petroleum refinery, Tüpraş was established there in 1960. The region also includes TUBITAK Marmara Research Centre, universities, industrial zones, public institutions and two techno-parks which are specialized on the automotive industry. The aim of this paper is to understand whether automotive cluster in this region is innovative. For this purpose local dynamics which affect evolution of the cluster is explained and characteristics of innovation of automotive firms in the region is clarified by a recent survey* held in 2008. The provinces in which the survey is done are Istanbul, Bursa, Kocaeli and Sakarya. * The area survey titled "Explaining Interrelation of Innovativeness and Competitiveness Considering Sub-Regions" is supported by ITU Research Fund. (2008 - 32458)
Keywords: 330; Automotive; Turkey; Istanbul; Eastern Marmara Region; cluster; innovativeness